Fostering Faith and Flourishing: A Phenomenological Inquiry into the Lived Experiences of Non-Catholic Graduating Students in a Catholic University - Junsay Jr., Feddy B.; Madrigal , Dennis (Technium Social Sciences Journal, 2024)
This phenomenological study explores the lived experiences of non-Catholic graduating students at a Catholic university in Bacolod City, Philippines. The research aimed to understand their insights and perspectives on studying within a Catholic institution. The study involved in-depth interviews with eight participants from diverse religious backgrounds. The findings revealed four key themes: spiritual growth, community and inclusivity, personal growth and resilience, and academic excellence and holistic development. The study highlights the positive impact of the university's inclusive environment, fostering spiritual growth through interfaith dialogue and religious education. The emphasis on community and shared values creates a sense of belonging and acceptance for non-Catholic students. The university's rigorous academic programs and supportive community contribute to personal growth, resilience, and academic excellence. The study concludes that the integration of non-Catholic students into Catholic universities fosters inclusivity, personal growth, and academic success, providing valuable insights for enhancing educational practices and promoting interfaith understanding.